Design and Rolling Analysis of a Novel Deformable Polyhedron Robot. (29th October 2014) - Tian, Yaobin; Wei, Xiangzhi; Joneja, Ajay; Yao, Yan-An
In this paper, a new rolling robot is proposed. The mechanism of the robot consists of eight links with three degrees of freedom (DOFs). The shape of each link of the robot is an equilateral triangle. The robot realizes its direction switching function by deforming into different modes of planar parallelogram mechanisms (PPM). In any deterministic mode, the robot can roll on the ground. The motion of the robot is studied based on the kinematic and zero moment point (ZMP) analyses. Though the robot has three DOFs, we show that it can realize flexible mobility via direction switching and rolling functions with two DOFs and one DOF, respectively. A prototype robot was manufactured. A series of simulations and experiments done using this prototype is reported, verifying the feasibility of the design.